Effect of the rigid constraint body thickness on aluminum alloy powder compact via hot isostatic pressing. (January 2019) - Huang, Xina; Lang, Lihui; Wang, Gang; Duan, Wen
This work investigated the effects of the rigid constraint body thickness on the mechanical properties and densification of hot isostatic pressing–produced 2A12 aluminum alloy powder compact. With the decrease in the rigid constraint body thickness, the tensile and yield strengths of the powder compact are improved; in addition, the radial and axial displacements increase. These phenomena can be attributed to the decrease in the isostatic pressure shielded by the rigid constraint body. The shielded isostatic pressure is found to be proportional to the rigid constraint body thickness, and therefore, the decrease in the rigid constraint body thickness gives rise to a reduction in the shielded isostatic pressure and enhances the tensile and yield strength properties of the 2A12 powder compact. However, the rigid constraint body thickness has a minor impact on the relative density of powder compact. The fracture morphology of tensile specimens was also studied by scanning electron microscope, and it shows the brittle fracture characteristics.